Thrust together : The Netherlands relationship with its Caribbean partners. - HOEFTE, Rosemarijn (1996)
Explores political developments in the Netherlands, Suriname and the Netherlands Antilles which have affected relations between these partners in recent years. While Suriname became independent, the people of the Netherlands Antilles opted to remain part of the Kingdom of the Netherlands, and Aruba, in April 1995, officially cancelled the date that had been set for its proposed independence - 1 January 1996.